PENGARUH CAREER INTERVENTION PROGRAM DALAM PENGAMBILAN KEPUTUSAN KARIR SISWA KELAS XII DI SURABAYA - Yuliati, Nurita; Tjahjoanggoro, A. J. (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Self-readiness of students in determining career choices after graduating from high school becomes the initial provision in the career preparation process. This readiness relates to self-confidence in the abilities of each student in every career decision-making process. Students who are confident in their abilities will easily make choices. However, researchers still find that many students are confused when asked about their plans after graduating from high school. One of the factors that have an impact on the career planning process is the lack of career information, feeling unprepared, and the lack of ability to manage emotions. For this reason, it is necessary to have interventions that can help students to be confident in making career decisions, in the form of training. This study aims to determine the effectiveness of a career intervention program to assist high school students in planning a career after graduating from school. The research subjects consisted of 48 high school students who were selected using a proposive sampling technique with the criteria of students having high CDDQ scores. The chosen method is pre experimental with one group pre test post test design. Data collection used the Career decision making difficult questionnaire (CDDQ) and Career Decision Self Efficacy Short term (CDSD-SF). The results of the analysis of the paired sample t test showed that there was a significant difference in the pre-test and post-test values. Thus, the career intervention program has a positive influence in helping class XII students make career decisions.